Bioassay-guided isolation and UHPLC-DAD-ESI-MS/MS quantification of potential anti-inflammatory phenolic compounds from flowers of Inula montana L. (15th November 2018) - Garayev, Elnur; Di Giorgio, Carole; Herbette, Gaëtan; Mabrouki, Fathi; Chiffolleau, Philippe; Roux, David; Sallanon, Huguette; Ollivier, Evelyne; Elias, Riad; Baghdikian, Béatrice
Abstract: Ethnopharmacological relevance: Flowers of Inula montana L. (Asteraceae), commonly known as "Arnica de Provence", are used in the traditional medicine of Provence in France with the same indication as Arnica montana, for the relief of bruises, as an anti-inflammatory agent. Aims of the study: The aim of our study is to evaluate its anti-inflammatory properties and to justify its traditional uses. Its potential valorization is evaluated in order to propose Inula montana as an alternative to Arnica montana . Materials and methods: Bio-guided fractionation of ethanolic extract allowed the isolation of compounds responsible of the inhibition of NO production. The fractionation was realized using chromatographic techniques and structure elucidation was conducted by ESI-MS and NMR spectral data. Anti-inflammatory effect of ethanolic extract, different fractions and isolated pure compounds was studied in vitro on immortalized mouse macrophages RAW 264.7. An analytical UHPLC-DAD-ESI-MS/MS method was developed for the identification of these compounds in the herbal drug. This UHPLC-DAD method was validated and was used to compare the phenolic profile and content in plant material from the two collection sites: Bonnieux and Merindol. Results: Eleven compounds were identified by UHPLC-MS. Chlorogenic acid (1 ), Luteolin (2 ), Nepetin (3 ), 3, 5- O -Dicaffeoylquinic acid (4 ), 1, 5- O -Dicaffeoylquinic acid (5 ), Nepitrin (6 ), Hispiduloside (7 ) and Jaceosid (8 ) were isolated and identified by NMR. Compounds9, 10 and11 were confirmed to be 6-Hydroxykaempferol 3, 7-dimethyl ether, Hispidulin and Chrysosplenol C, respectively by comparing retention times and MS/MS data with those of the authentic substances. Six compounds:1 and4 –8 are reported for the first time in Inula montana L. Compounds2 –8 showed promising anti-inflammatory activity with the release of NO with IC50 value < 7 µM. The UHPLC- DAD method of quantification of three major bioactive compounds (1, 3 and5 ) was validated. Conclusion: Flowers extracts and isolated compounds present promising anti-inflammatory activity which provides a scientific basis for the traditional use of Inula montana and may be proposed in the same indications as Arnica montana . The developed and validated simple, accurate and rapid UHPLC method can be used for the quality control of the herbal drug. Graphical abstract: